PENERAPAN MANOVA DALAM ANALISIS HUBUNGAN ANTARA LUAS WILAYAH DENGAN CAKUPAN VAKSINASI COVID-19 DI PROVINSI KALIMANTAN SELATAN - Muhammad Fadhil Rasyidin; Dewi Anggraini; Hidayatullah Muttaqin (RAGAM: Journal of Statistics & Its Application, 2023)
In Indonesia, the problem with the spread of COVID-19 is 1.35 million with 1.17 million recovered and 36,721 deaths as of March 5, 2021. From the data on the spread of COVID-19, it can be seen from the length of time that has passed, the number of cases has increased. Sinovac (CoronaVac) is a vaccine for COVID-19 produced by the Sinovac company, using inactivated virus technology or utilizing attenuated viruses. The coverage of vaccines for dose 1 and dose 2 in South Kalimantan Province is low compared to other provinces, even though South Kalimantan Province is a province that is classified as having the smallest area among other provinces included in Kalimantan Island. The purpose of the study was to find out the relationship between area and coverage of COVID-19 vaccination in South Kalimantan Province. This study uses One-Way Manova because it analyzes one predictor variable, in the form of area and three response variables simultaneously, in the form of COVID-19 vaccination coverage based on the vaccination target category: health human resources, public officers and the elderly. The results of the study using the One-Way MANOVA method showed the Pillai's Trace value of 0.020. The results of the multivariate significance test obtained by Wilk's Lambda   so that it rejects  which means that the significant model or area () has an influence on vaccination coverage (). Based on alleged multivariate regression model and the results of the MANOVA test, both are directly proportional, namely there is a significant relationship that area area has an influence on COVID-19 vaccination coverage. Large areas have vaccination coverage that tends to be low when compared to small areas. Vaccination distribution for a small area can be said to be more efficient than other broad categories and for elderly vaccine recipients, it is lower than the category of vaccine recipients for public officials and health human resources